SHM of single lap adhesive joints using subharmonic frequencies. (12th September 2017) - Ginzburg, D; Ciampa, F; Scarselli, G; Meo, M
Abstract: The increased usage of adhesive bonding as a joining method in modern aerospace components has led to developing reliable ultrasonic health monitoring systems for detection of regions of poor adhesion. Nonlinear acousto-ultrasonic techniques based on higher harmonics and subharmonic frequencies have shown to be sensitive to the detection of micro-voids and disbonds. Nonlinear resonance properties of disbonds generate various nonlinear phenomena such as self-modulation, subharmonics, hysteresis and so on. By exploiting the local natures of these phenomena, this paper demonstrates the use of subharmonics for detection and imaging of flaws in bonded structures. To optimise the experimental testing a two-dimensional analytical model and a three-dimensional finite element analysis simulation were developed for understanding the generation of nonlinear elastic effects with emphasis on subharmonic frequency components. The proposed analytical model qualitatively described the generation of subharmonics but also higher harmonics due to the nonlinear intermodulation of the driving and resonance frequencies associated with the disbonded region. The numerical model was developed by modifying the user defined cohesive element formulation with a bi-linear traction-displacement relationship in order to simulate the interaction of elastic waves with the structural disbond. Whilst the analytical model supported the selection of the driving frequency, the numerical one successfully predicted the generation of subharmonic frequencies originating in the disbonded area. Experimental tests were conducted on a disbonded single lap joint structure using surface-bonded piezoelectric transducers and a laser-Doppler vibrometer, and allowed to validate the analytical and numerical results. It was clearly demonstrated that the nonlinear resonance effects in the form of subharmonics could be used to discriminate reliably regions of poor adhesion in bonded structures. This work can lead to new in situ nonlinear acoustic based health monitoring system for locating and imaging defects in critical aerospace components.